Parametric Study of a Soil Erosion Control Technique: Concrete Lozenges Channels - Latifa El Bouanani; Khadija Baba; Ghizlane Ardouz; Fatima Ezzahraa Latifi (Civil Engineering Journal, 2022)
A new technique, "the concrete lozenges channels" is described in this paper. It is an erosion control measure to attenuate the water soil loss quantity to a tolerable level. These are open inclined channels that form lozenges on the slope. In fact, they drain rainfall, runoff, and sediments alongside the slope into the ditch. Using the RUSLE erosion model for erosion assessment, the parameters that had the most influence on the percentage decrease of the soil erodibility are discussed. A comparison between techniques already used, that is, the concrete arches and the concrete lozenge channels proposed in this paper, makes it possible to mention the shortcomings and the strengths of each technique. In fact, the percentage decrease in erosion soil loss is about 42% for 2 arches and is about 49% for 2 lozenges. If the number of channels present on the slope increases, the area exposed to erosion decreases. By comparing the study case, the exposed area for one lozenge is less by 39% to 68% than the exposed area for one arch. The total perimeter lengths are comparable. In this article, a parametric study is undertaken to define the optimum dimensions and optimum number of concrete inclined channels. The ditch section and the inclined channel section are determining factors in the lozenge sizing. Doi: 10.28991/CEJ-2022-08-09-09 Full Text: PDF